(Acetonitrile-κN)(2-(diphenylphosphanyl)ethanamine-κ2N,P)((1,2,3,4,5-η)-1,2,3,4,5-pentamethylcyclopentadienyl)iron(II) hexafluoridophosphate tetrahydrofuran monosolvate - Lee, Kajin; Rominger, Frank; Limbach, Michael (Acta crystallographica. Section E, Crystallographic communications, 2011)
In the title cationic Cp*Fe(II) complex, [Fe(C10H15)(CH3CN)(C14H16NP)]PF6·C4H8O, the metal ion is coordinated by the η5-Cp* ring as well as the P and N atoms of the chelating 2-(diphenylphosphino)ethylamine ligand and an additional acetonitrile molecule in a piano-chair conformation. The PF6− anion is disordered over two sets of sites with occupancies of 0.779 (7) and 0.221 (7).